2016
DOI: 10.1080/15017419.2016.1264467
|View full text |Cite
|
Sign up to set email alerts
|

Disability leisure: in what kind of activities, and when and how do youths with intellectual disabilities participate?

Abstract: The article examines what kind of activities youths with intellectual disabilities participate in during their leisure time, and when and how they participate. The analysis is based on qualitative interviews of ten youths with intellectual disabilities (aged 13-16 years) and their parents (N=20). The study reveals that intellectually disabled youths have the same preferences and wishes for leisure activities as their non-disabled peers. Both genders prefer sports and cultural activities. However, a closer exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
39
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 24 publications
3
39
0
1
Order By: Relevance
“…The findings of our study also revealed that three out of four participants spent a better time and thus participated more in leisure time activities which they selected themselves. In this respect, the findings of the study carried out by Melboe and Ytterhus (2016) are similar to the findings of this study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The findings of our study also revealed that three out of four participants spent a better time and thus participated more in leisure time activities which they selected themselves. In this respect, the findings of the study carried out by Melboe and Ytterhus (2016) are similar to the findings of this study.…”
Section: Discussionsupporting
confidence: 89%
“…In a study, Melboe and Ytterhus (2016) researched into the types of leisure activities that young individuals with intellectual disabilities chose and engaged in. They found out that those individuals had a higher quality time that they spent in a more fruitful and enjoyable way while doing leisure activities they decided on.…”
Section: Discussionmentioning
confidence: 99%
“…The “arranged company pattern” provides insight into the dominant role of support persons in the social life of many respondents. Since adolescents with a disability may have the same leisure preferences as their non‐disabled peers (Melbøe & Ytterhus, ), they shared desired activities or events with their support person. Consequently, support persons may be essential facilitators as well as barriers to leisure participation (Mahy, Shields, Taylor, & Dodd, ).…”
Section: Discussionmentioning
confidence: 99%
“…The social life of adolescents with intellectual disability involves a smaller number of friends and fewer close friendships than with adolescents without disabilities (Solish, Perry, & Minnes, ; Søderstrøm & Tøssebro, ; Tipton, Christensen, & Blacher, ). They spend less time with friends outside school than others (Melbøe & Ytterhus, ; Solish et al, ), and fewer friends visit them at home (D'Haem, ; Dolva, Kleiven, & Kollstad, ). Commonly, their friends also have a disability and have been considered a friend for a long time (McVilly, Stancliffe, Parmenter, & Burton‐Smith, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation